Research progress in brain-targeted nasal drug delivery - Huang, Qingqing; Chen, Xin; Yu, Sixun; Gong, Gu; Shu, Haifeng (Frontiers in Aging Neuroscience, 2024)
The unique anatomical and physiological connections between the nasal cavity and brain provide a pathway for bypassing the blood-brain barrier to allow for direct braintargeted drug delivery through nasal administration. There are several advantages of nasal administration compared with other routes; for example, the first-pass effect that leads to the metabolism of orally administered drugs can be bypassed, and the poor compliance associated with injections can be minimized. Nasal administration can also help maximize brain-targeted drug delivery, allowing for high pharmacological